Cell-mediated immunity and expression of MHC class I and class II molecules in dogs naturally infected by canine transmissible venereal tumor: Is there complete spontaneous regression outside the experimental CTVT? - do Prado Duzanski, Anderson [UNESP]; Flórez, Luis Mauricio Montoya [UNESP]; Fêo, Haline Ballestero [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Kaneno, Ramon [UNESP]; Rocha, Noeme Sousa [UNESP] (Elsevier, 2022)
The canine transmissible venereal tumor (CTVT) is a transplantable cancer with the ability evade the immune system, despite strict immune surveillance of the host; in this context, the relationship between inflammatory infiltrate and CTVT prognosis is not entirely understood. Natural canine transmissible venereal tumors of 22 dogs were evaluated for tumor/host interaction through clinical and epidemiological data, cyto-histopathological and cytogenetic findings and, mainly, cell-mediated immune response. We performed analysis on dogs with naturally acquired disease to provide information from the study of CTVT biology in its natural course, as the clinical evolution of the natural tumor in the host is not yet as well known as in the laboratory. Populations for T cell labeling (CD3+ CD4+ CD8+), B cells, NK cells, and macrophages were analyzed by flow cytometry in blood and tumor samples and expressions of MHC class I and class II molecules were quantified by immunohistochemistry and compared mainly between the phases of progression and regression in the natural CTVT. Dogs were also treated with vincristine sulfate and evaluated for chemotherapeutic response. Chemotherapy was effective in 88% of cases and there was no recurrence of the disease 12 months after the cure. Tumor cells displayed a numerical chromosomal variation between 54 and 72, not correlating with the host genotype. Although a greater expression of MHC molecules [18.6 ± 5.8% class I (P < 0.004) and 38.5 ± 6.5% class II (P < 0.003)] was observed in the regression phase, no significant effect was observed between the clinical phase of the tumor and cellular immune response in the analysis by flow cytometry (P > 0.05). We also found no correlation between cytological subtype of the tumor (plasmacytoid, lymphocytoid and mixed) and cellular immune response, suggesting that there is no difference in tumor immunogenicity. Here, we found no immunological evidence to support the theory of the immune-induced complete spontaneous regression in CTVT.
Keywords: Chemotherapy; CTVT; Dog; Flow cytometry; Regression; Tumor immunity